PENGARUH KEMAMPUAN KERJA DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN KONAWE UTARA - Ekawati Ekawati; Nasrul Nasrul; Sriwiyati Mahrani (Pascasarjana Universitas Halu Oleo, 2017)
This study aimed to: 1) analyze the effect of work ability simultaneously with job characteriscs on staff’s performance, 2) analyze the effect of work ability on staff’s performance;3) analyze the effect of job characteristics on staff’s performance. objects of the study were the board of Local Finance and Assets management (BPKAD) of North Konawe regency. Population of the study included all staff of BPKAD of North Konawe regency, totaling 44 staff. Samples were determined using a census technique, therefore all population became the samples. Data were collected using a questionnaire. The data were analyzed using the multiple linear regression analysis that was performed on the SPSS version 20.Results showed that:1) simultaneously work ability and job characteristics had a positively significant effect on staff’s performance;2) work ability had a positively significant effect on staff’s performance;3) job characteristics had a positively significant effect on staff’s performance